(untitled) (Texas Journal of Medical Science, 2023)
The article presents the results of clinical studies on the development of a method for local intraoperative hemostasis and improvement of reparative processes during operations on the thyroid gland. For clinical evaluation of the effectiveness of the proposed method, two study groups were formed for 237 patients with mixed, nodular and diffuse toxic goiter. The main group consisted of 98 patients, and the comparison group - 139. In the main group of operated patients, hemostasis was carried out according to the method developed by us, and in the comparison group, by traditional methods. Surgery included thyroidectomy, hemithyroidectomy, and subtotal thyroidectomy. In the main group of patients, for the purpose of hemostasis, Hemoben powder crystals with a size of 25-50 microns were used at the rate of 200 mg per area of 8-9 cm2, which was applied over the wound with a thin layer until a thin translucent film was formed, followed by irradiation of the wound with low-energy laser radiation (Sogdiana apparatus) with a wavelength of 0.89 microns, a frequency of 500 Hz for 2 minutes at a distance of 5 cm from the wound; then, for 5-7 days, percutaneous irradiation sessions with the same laser at a frequency of 80 Hz were performed daily in the projection of the surgical wound. The study showed that the use of the domestic hemostatic agent Hemoben provides complete hemostasis, and the addition of the technique by treating the surgical field with low-intensity laser radiation enhances the reparative properties of the drug. The proposed method for local hemostasis and improvement of reparative processes during thyroid surgery is characterized by a quick, effective and stable stop of bleeding, prevents the development of lymphohemorrhagic complications, and also reduces the frequency of early postoperative complications due to intra- and postoperative laser exposure.